Peningkatan Kemandirian Dan Hasil Belajar IPA MelaluiStrategi Course Review Horay Pada Siswa Kelas V SD Negeri 03 Bangsri Tahun Pelajaran 2015/2016 - Maryadi, Aditiya (2016)
The teacher has the main task in determining the quality of learning, by formulating an appropriate way to achieve student success in learning. Research objectives are: (1) to increase the independence of student learning through strategies Course Review Horay, (2) to improve student learning outcomes through strategies Course Review Horay. This type of research is classroom action research with the research design consists of four stages: planning, implementation, observation, and reflection. The subjects of this study were teachers and students of class V Elementary School 03 Bangsri totaling 29 students. The technique of collecting data through observation, interviews, tests and documentation. Data analysis techniques used are: reduction, description, and conclusions. The results showed an increase in independent learning and student learning outcomes. Improved learning independence as follows: (a) Confidence 25 students or 86%, (b) Responsibilities of the assignment of teachers 26 students or 90%, (c) Discipline following study of 24 students or 83%, (d) Focus on learning and understand the material 26 students or 90%. Improving student learning outcomes is 25 students or 86% of students who completed the average value of learning outcomes, namely 81.29. The conclusion is through the implementation of strategies Course Review Horay can improve the independence and learning outcomes Elementary School fifth grade students 03 Bangsri year 2015/2016.